2011
DOI: 10.1097/pcc.0b013e3181f36f6e
|View full text |Cite
|
Sign up to set email alerts
|

First responder performance in pediatric trauma: A comparison with an adult cohort*

Abstract: Prehospital care of children is suboptimal compared with adults in areas of endotracheal intubation, establishment of peripheral intravenous access, and fluid resuscitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 10 publications
1
26
0
1
Order By: Relevance
“…14Y16 Evidence suggests that first responders have more difficulty with pediatric trauma than do adults. 16 No statewide data on such factors, however, are available for use. At the population level, vPTC1s correlate with decreasing statewide mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14Y16 Evidence suggests that first responders have more difficulty with pediatric trauma than do adults. 16 No statewide data on such factors, however, are available for use. At the population level, vPTC1s correlate with decreasing statewide mortality.…”
Section: Discussionmentioning
confidence: 99%
“…14 In addition, several articles suggest prehospital care of pediatric trauma patients may be inferior to similar adult trauma patients in some areas. 15,16 Overall, an impact of pediatric trauma centers has been difficult to measure.…”
mentioning
confidence: 99%
“…In their discussion the authors suggest that EMS providers receive insufficient training and practice with these challenging skills and that this may account for the discrepancy. [8]…”
Section: Pediatric Ems Systems and Performancementioning
confidence: 99%
“…12,13,25Y31 Bankole et al 32 questioned this practice by showing that pediatric patients had significantly more difficulties with PHI when compared with adults. Multiple other studies have indicated that airway PHIs have been detrimental to mortality and functional outcome when compared with manual bag mask ventilation.…”
Section: Discussionmentioning
confidence: 95%